Development of a Local Wisdom-Based Android Web-Learning Model for Digital Literacy Skills and Student Self-Confidence in the Digital Learning Era - Anda Saputra; Khairunnisa Khairunnisa (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This research aims to develop an Android-based web-learning model integrating Minangkabau local wisdom to improve students' digital literacy skills and self-confidence in the digital learning era. The research employed a Research and Development method with the 4D model (Define, Design, Develop, Disseminate). During the definition phase, a survey was conducted with 100 students at ISI Padangpanjang to identify their levels of digital literacy and self-confidence. The design phase focused on developing learning syntax, designing the application interface, and integrating local cultural values. The product was developed as an Android application, then validated by three experts, tested for practicality by 20 students and two lecturers, and tested for effectiveness using a pretest-posttest design. The results showed that the developed model achieved an average validity score of 90.2%, categorized as very valid. The practicality test yielded an average score of 90.3% from both students and lecturers, categorized as very practical. Effectiveness testing using a paired t-test showed a significant increase in digital literacy (t = 8.52; p = 0.000) and student self-confidence (t = 9.01; p = 0.000). These findings demonstrate that integrating technology with local cultural values can create meaningful learning experiences, improve digital skills, and strengthen students' character. This research highlights the importance of digital learning innovations that are not solely technically oriented but also rooted in cultural values, thus supporting the Freedom to Learn policy and strengthening student identity in the digital age.